Analisis Pembelajaran Sosial Emosional Di Era Pembelajaran Abad 21 Pada SD Negeri 101764 Kecamatan Percut Sei Tuan - Rifa Atul Suaidah Lubis (Universitas Negeri Malang, 2023)
Abstract: This study aims to determine social-emotional learning in SD Negeri 101764Percut Sei Tuan District, to determine the ability of teachers to design social-emotional learning in the 21st century learning era, and to determine students' social-emotional competence. The research method used in this study is descriptive qualitative with field studies conducted at SD Negeri 101764, Percut Sei Tuan District, Deli Serdang Regency. Data collection techniques using observation and questionnaires. The results of this study indicate that: 1) Based on the analysis of social emotional learning in the 21st century learning era at SD Negeri 101764, Percut Sei Tuan District, for the 2021/2022 academic year, the research results show that the social emotional learning process is categorized as low. 2) The recapitulation results of teacher activity observation sheets obtained 59.21% were categorized as sufficient and the results of student activity observation sheet recapitulation obtained 65.45% were categorized as sufficient. 3) The results of the recapitulation of students emotional social competence of 67,50% are categorized as sufficient.Keywords: Social emotional learning, 21st century learningAbstrak: Penelitian ini bertujuan untuk mengetahui pembelajaran sosial emosional di SD Negeri 101764 Kecamatan Percut Sei Tuan, mengetahui kemampuan guru dalam merancang pembelajaran sosial emosional di era pembelajaran abad 21, serta mengetahui kompetensi sosial emosional peserta didik. Adapun Metode penelitian yang digunakan dalam penelitian ini adalah Kualitatif deskriptif dengan studi lapangan yang dilakukan di SD Negeri 101764 Kecamatan Percut Sei Tuan Kabupaten Deli Serdang. Teknik pengumpulan data menggunakan observasi dan kuesioner. Hasil penelitian ini menunjukkan bahwa: 1) Berdasarkan analisis pembelajaran sosial emosional di era pembelajaran abad 21 di SDNegeri 101764 Kecamatan Percut Sei Tuan Tahun Pelajaran 2021/2022 pada hasil penelitian, diperoleh gambaran yaitu proses pembelajaran sosial emosional dikategorikan rendah. 2) Hasil rekapitulasi lembar observasi aktivitas guru diperoleh 59,21% dikategorikan cukup dan hasil rekapitulasi lembar observasi aktivitas siswa diperoleh 65,45% dikategorikan cukup. 3) Hasil rekapitulasi kompetensi sosial emosional peserta didik sebesar 67,50% dikategorikan cukup.Kata kunci: Pembelajaran sosial emosional,pembelajaran abad 21.